Early versus late institution of plasma exchange therapy in pregnancy induced thrombotic microangiopathy and its effects on clinical outcomes–A case series. (February 2018) - Kaul, Anupama; Vishwakarma, Kavita; Bhaduaria, Dharmendra Singh; Mishra, Prabhaker; Prasad, Narayan; Jain, Manoj; Thammshetti, Venkatesh; Patel, Manas R.; Gupta, Amit; Sharma, Raj Kumar
Abstract: Purpose: To look for incidence of pregnancy associated TMA, clinical presentation and impact of early diagnosis and institution of plasma exchange on overall renal outcomes Methods: −This is a retrospective study among all female patients who presented with acute kidney injury post pregnancy between October 2002 to April 2016 in department of nephrology in a tertiary care hospital in northern India and diagnosed as pregnancy induced TMA. The patient were assessed for duration of onset of renal failure to time of diagnosis of TMA, role of modality of treatment ie plasmpaharesis to outcome. These patients were assessed for complete, partial or no recovery in renal functions at 60 days after admission. Results: Patients whose time of onset of renal failure to a correct diagnosis of TMA was ≤15 days and age less than 30 years was also associated with good prognosis. The patients who received plasma exchange and that to within 72 h of admission had more chances of recovery. Conclusions: Early diagnosis of disease and early institution of plasma exchange therapy improves renal outcomes in postpartum TMA